From San Francisco Eastward : Victorian Theater in the American West - Eichin, Carolyn Grattan, 1951- (Book collections on Project MUSE., 2020)
"This is a study of theater in the hinterlands of the American West. In clear prose the author takes the reader through the ups and downs of an economic rollercoaster of theatrical strategies and personalities ever changing to meet the unique challenges of the region"--